Equine-Assisted Therapy for Veterans with PTSD: Manual Development and Preliminary Findings. Issue 5 (8th February 2020) - Arnon, Shay; Fisher, Prudence W; Pickover, Alison; Lowell, Ari; Turner, J Blake; Hilburn, Anne; Jacob-McVey, Jody; Malajian, Bonnie E; Farber, Debra G; Hamilton, Jane F; Hamilton, Allan; Markowitz, John C; et al.
Abstract: Introduction: Equine-assisted therapy (EAT) for post-traumatic stress disorder (PTSD) has attracted great interest despite lacking empirical support, a manual, and a standardized protocol. Our team of experts in EAT and PTSD developed an eight-session group EAT treatment protocol for PTSD (EAT-PTSD) and administered it to two pilot groups of military veterans to assess initial effects. Materials and Methods: We describe the development of the treatment manual, which was used with two pilot groups of veterans. Protocol safety, feasibility, and acceptability were assessed by reported adverse events, treatment completion rates, and self-rated patient satisfaction. Preliminary data on PTSD, depressive, and anxiety symptoms and quality of life were collected pretreatment, midpoint, post-treatment, and at 3-month follow up. Results: No adverse events were recorded. All patients completed treatment, reporting high satisfaction. Preliminary data showed decreases in clinician-assessed PTSD and depressive symptoms from pre to post-treatment and follow-up (medium to large effect sizes, d =  .54–1.8), with similar trends across self-report measures ( d =  0.72–1.6). In our pilot sample, treatment response and remission varied; all patients showed some benefit post-treatment, but gains did not persist at follow-up. Conclusions: This article presents the first standardized EAT protocol. Highly preliminary results suggest our new manualized group EAT-PTSD appears safe, well-regarded, and well-attended, yielding short-term benefits in symptomatology and quality of life if unclear length of effect. Future research should test this alternative treatment for PTSD more rigorously.